Clinical effectiveness of short course oral prednisone for stricture prevention after semi-circumferential esophageal endoscopic submucosal dissection - Arantes, Vitor N.; Ramos, Josué Aliaga; White, Jonathan Richard; Parra-Blanco, Adolfo (Endoscopy International Open, 2022)
Background and study aims Esophageal strictures (ES) occur frequently after semi-circumferential endoscopic submucosal dissection (ESD) for the eradication of superficial esophageal neoplasms and negatively impact a patient’s quality of life. Oral corticosteroids have been shown to be clinically effective, but the most appropriate drug, dose and duration is yet to be determined. The aim of the study was to investigate the clinical effectiveness and safety of 30 mg prednisone with a shortened tapering schedule on ES after semi-circumferential ESD.Patients and methods This was a retrospective observational study that analyzed consecutive patients with esophageal neoplasms who underwent semi-circumferential ESD with a resection defect greater than 75 % of the circumference that received a protocol of oral steroids for stricture prevention. On postoperative day 3, 30 mg prednisone was prescribed, tapering weekly to 20 mg/10 mg/5 mg over 4 weeks. Follow-up included clinic consultation and endoscopic review at weeks 2 and 4. Effectiveness outcomes included ES rates, safety, tolerability, resection, dilatation and recurrence rates.Results Ninety ESD procedures were carried out during the specified time period and 18 patients met the inclusion criteria for the final analysis. The mean age was 61.5 years, lesion size was 52.5 mm, and final histology was squamous cell carcinoma in all patients. Incidence of intra-procedure complications was: bleeding 5.5 % (1/18) and ES 5.5 % (1/18), requiring a median two endoscopic dilatations. En bloc, R0 and curative resection rates were 88.8 %, 72.2 %, and 55.5 %, respectively.Conclusions The short tapering schedule of 30 mg oral prednisone is clinically efficacious and safe for prevention of ES after semi-circumferential ESD in Latin American patients.